Gluten protein composition and aggregation properties as predictors for bread volume of common wheat, spelt, durum wheat, emmer and einkorn. (September 2018) - Geisslitz, Sabrina; Wieser, Herbert; Scherf, Katharina Anne; Koehler, Peter
Abstract: The technological properties of the ancient wheat species spelt, emmer and einkorn are considered inferior compared to common wheat and durum wheat, but there are only few comparative studies between ancient and modern wheat species. To help fill this gap, protein content and composition, gluten aggregation, dough and bread properties were determined in a unique set of eight cultivars each of common wheat, spelt, durum wheat, emmer and einkorn grown under standardized conditions at one location in the same year. Spearman correlations and principal component analysis (PCA) revealed that especially the contents of glutenins, high-molecular-weight glutenin subunits and glutenin macropolymer were suitable to predict the volume of breads made from wholemeal flours of the five wheat species using microbaking tests. Based on their proximity to common wheat in the PCA, one cultivar each of spelt, emmer and einkorn was identified that had similar protein analytical, functional and baking properties to common wheat. Furthermore, the characterization of gluten aggregation behavior using the GlutoPeak test (GPT) enabled an estimation of dough properties and bread volume. Therefore, the fast and easy GPT may serve as an alternative to time-consuming and labor-intensive baking tests. Highlights: A unique set of eight cultivars of wheat, spelt, wheat, emmer and einkorn was compared. Quality parameters to predict the baking quality of wholemeal flours were defined. Contents of polymeric gluten proteins were good predictors of the baking quality. Spelt, emmer and einkorn cultivars with good baking quality were identified by PCA. The GlutoPeak test enabled an estimation of dough properties and bread volume.